Legal Reconstruction of Local Government Responsibility in Ensuring Equitable Access to Clean Water through Sea Water Reverse Osmosis Governance in Gili Trawangan - Muhamad Husni; Siti Hasanah; Nurjannah Septyanun; Firzhal Arzhi Jiwantara (The Easta Journal Law and Human Rights, 2026)
Freshwater scarcity in small island regions has become a significant governance challenge, particularly in balancing community needs, tourism development, and environmental sustainability. Gili Trawangan faces increasing demand for clean water due to limited freshwater resources and rapid tourism growth, requiring innovative and equitable water management strategies. This study aims to analyze the legal responsibility of local governments in ensuring equitable access to clean water through the utilization of Seawater Reverse Osmosis (SWRO) technology, focusing on distributive justice, public accountability, and sustainable resource governance. This research employs an empirical socio-legal method by integrating statutory analysis with qualitative field research. Data were collected through interviews, observations, and documentation, and analyzed using qualitative descriptive analysis supported by data triangulation. The findings show that SWRO implementation through cooperation between the North Lombok Regency Government, the Regional Water Supply Company (PDAM), and the private sector has contributed to addressing clean water scarcity in Gili Trawangan. However, several challenges remain, including unequal water distribution, limited production capacity, tariff mechanisms, institutional accountability, and potential conflicts between local community needs and tourism industry demands. This study argues that clean water governance should not only emphasize technological efficiency but also prioritize justice, affordability, environmental sustainability, and protection of public rights. The novelty of this research lies in developing a socio-legal perspective that positions SWRO technology as a governance instrument for achieving water justice rather than merely a technical solution for freshwater scarcity.